2001
DOI: 10.1053/jhep.2001.24432
|View full text |Cite
|
Sign up to set email alerts
|

Steatosis Accelerates the Progression of Liver Damage of Chronic Hepatitis C Patients and Correlates With Specific Hcv Genotype and Visceral Obesity

Abstract: The role of steatosis in the progression of liver damage in chronic hepatitis C (CHC) was studied. Enrolled were 180 consecutive liver biopsy-proven CHC patients and 41 additional subjects with a known duration of infection. We evaluated the histological activity index (HAI), grade of fibrosis and steatosis, body mass index (BMI; kg/m 2 ), distribution of body fat, HCV genotype, and levels of HCV RNA. Eighty six (48%) patients showed steatosis, and a higher prevalence was observed in genotype 3a infection (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
791
15
28

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 971 publications
(904 citation statements)
references
References 33 publications
70
791
15
28
Order By: Relevance
“…Our finding of HCV G3-specific perturbation of cholesterol metabolism is consistent with the clinical observations of increased prevalence of metabolic sequelae relative to other HCV genotypes, including more significant hypocholesterolemia, and increased rates and severity of hepatic steatosis 5,10 that also inversely correlate with lower cholesterol for HCV G3 10 and differing effects on host metabolic gene expression. 13 In keeping with our observation of an association between HCV RNA and low cholesterol in HCV G3, intrahepatic G3 HCV RNA has also been shown to correlate directly with other metabolic consequences of infection such as steatosis, further supporting a possible direct viral pathogenic effect.…”
Section: Discussionsupporting
confidence: 88%
“…Our finding of HCV G3-specific perturbation of cholesterol metabolism is consistent with the clinical observations of increased prevalence of metabolic sequelae relative to other HCV genotypes, including more significant hypocholesterolemia, and increased rates and severity of hepatic steatosis 5,10 that also inversely correlate with lower cholesterol for HCV G3 10 and differing effects on host metabolic gene expression. 13 In keeping with our observation of an association between HCV RNA and low cholesterol in HCV G3, intrahepatic G3 HCV RNA has also been shown to correlate directly with other metabolic consequences of infection such as steatosis, further supporting a possible direct viral pathogenic effect.…”
Section: Discussionsupporting
confidence: 88%
“…The observation that some obese individuals presented a liver disease histologically indistinguishable from alcoholic liver disease itself had long been recognized. [42][43][44][45][46][47][48][49] Interestingly, it has been recently demonstrated that obesity also increases the risk of liver disease induced by either alcohol 50 or chronic hepatitis C. [51][52][53] In a literature survey of 41 original articles comprising information on liver morphology in 1515 morbidly obese patients, liver biopsy was considered as normal in only 12% of the cases. 54 The most frequent abnormality reported was fatty changes present in 80% of the biopsies; portal inflammation was also common (33%) while portal or periportal fibrosis was observed in 29%.…”
Section: The Association Of Nash With Obesitymentioning
confidence: 99%
“…[8][9][10][11][12] In the few general population-based surveys conducted, the prevalence of liver disease, particularly hepatic steatosis (fatty liver disease), also appears to be higher in heavier people. 13,14 However, as has been highlighted, 15 interpretation of these findings is complicated by the issue of reverse causality.…”
Section: Introductionmentioning
confidence: 99%